The predatory mite Stratiolaelaps scimitus as a control agent of the fungus gnat Bradysia matogrossensis in commercial production of the mushroom Agaricus bisporus - Castilho, Raphael C. [UNESP]; de Moraes, Gilberto J.; Silva, Edmilson S.; Freire, Renata A. P.; Da Eira, Frederico C. (Taylor & Francis Ltd, 2009)
We evaluated the potential effectiveness of the mite Stratiolaelaps scimitus (Womersley) in controlling populations of the sciarid fly Bradysia matogrossensis (Lane) in commercial production of the mushroom Agaricus bisporus (Lange). Two mushroom farm experimental tests were conducted: in the first, one of the treatments corresponded to two releases of the predator (immediately after inoculation of A. bisporus in the substrate and immediately after casing); in the second, one of the treatments corresponded to a single release of the predator (immediately after casing). In both cases, the contrasting treatment (control) represented the adoption of no measure to reduce the pest population. Pest population density was significantly lower, while yield of top quality mushroom was significantly higher in both predator release treatments than in the controls. Samples taken at the end of the tests suggested that the population density of S. scimitus increased in the mushroom bags during the course of the experiment. The results indicate that S. scimitus can effectively control B. matogrossensis in commercial mushroom production.
Keywords: predatory mite; Biological control; mushroom pest